Cost of Total Intravenous Anesthesia Versus Inhalation Anesthesia in Obstructive Sleep Apnea Surgery. (2nd March 2022) - Alnemri, Angela; Sussman, Sarah; Estephan, Leonard; Hamilton, Callum; Stewart, Matthew; Zhan, Tingting; Thaler, Adam; Ananth, Ashwin; Boon, Maurits; Huntley, Colin; Hunt, Patrick
ABSTRACT: Objectives: To compare cost and time spent in surgical and postoperative courses in patients with obstructive sleep apnea (OSA) undergoing surgery with either total intravenous anesthesia (TIVA) or inhalational anesthesia. Study Design: Retrospective chart review. Methods: Retrospective review on patients undergoing surgery for OSA under general anesthesia from January 2019 to October 2020. Cost per service was acquired for the day of surgery. Results: A total of 230 patients were included: 95 received TIVA; 135 received inhalation anesthesia. Total cost was significantly higher in the TIVA nasal surgery group by 286 ( P = .035). TIVA produced significantly higher pharmacy and operating room costs across all surgeries and OSA severities. These increased costs were offset by significantly lower supply costs in upper airway stimulator (UAS, −419.50; P = .007) and uvulopalatopharyngoplasty (UPPP, −115.16; P = .015) patients receiving TIVA. In the TIVA cohort, there was a trend toward lower recovery room costs after UAS (−111.09; P = .063) and nasal surgery (−64.45; P = .096) and anesthesia costs after nasal surgery (−36.67; P = .054). Total recovery time was reduced by 18 minutes ( P = .004) for nasal surgery, 25 minutes ( P = .043) for UAS, and 27 minutes ( P = .147) for UPPP patients receiving TIVA. Conclusion: When used in an outpatient setting for patients with OSA, TIVA adds to pharmacy and operating room costs, but this is usually offset by lower supply, anesthesia, and recovery room costs. We found decreased recovery times in the TIVA cohort. TIVA has proven benefits in patient outcomes and can be cost‐effective in OSA surgery. Level of Evidence: 3 Laryngoscope, 132:1487–1494, 2022